Evidence of Metallic Plating on Archaeological Artefacts by Voltammetry of Microparticles. (18th March 2014) - Ottenwelter, E.; Costa, V.
<x xml:space="preserve">Abstract</x> Voltammetry of microparticles using a paraffin‐impregnated graphite electrode (VMP/PIGE) was applied as a very local and non‐invasive analytical technique in order to investigate the presence of remains of metallic plating on two ferrous and one cuprous artefact from the medieval period. The analyses have been performed locally and selectively on regions presenting particular features, such as texture, cohesion and colour differences. The results confirm local differences in chemical composition, leading to conclusions about the presence of metallic plating on these artefacts.